Pemanfaatan Limbah Cair Pabrik Kelapa Sawit Sebagai Bioaktivator Untuk Pengomposan Tandan Kosong Kelapa Sawit - Zainudin Zainudin; Abdul Rofik (Agrifarm : Jurnal Ilmu Pertanian, 2019)
Palm oil is an export commodity of the plantation sector which began to develop rapidly in East Kalimantan with an area until 2017 reaching 1,192,342 Ha consisting of 284,523 Ha as plasma / smallholder plants, 14,402 Ha owned by SOEs as the core and 893,417 Ha owned by Large Private Plantation.Empty bunches (Tankos) are solid waste that is produced by palm oil mills in the process of managing palm fruit bunches into crude palm oil (CPO). In each processing 1 ton of fruit bunches will produce Tankos as much as 21-23%. Oil palm empty fruit bunches that are not managed properly will become waste that does not provide benefits. Compost technology using a local microorganism starter (MOL) can be used to produce quality organic fertilizer considering the process involves decomposing bacteria of organic ingredients. Compost technology from tankos waste is very possible to be developed, both at the level of farmers and private oil palm companies. This study aim to determine the potential of palm oil mill effluent (POME) as an bioactivator for composting oil palm empty fruit bunches, and to determine the chemical quality of oil palm empty fruit bunch compost with MOL bioactivator liquid waste as organic fertilizer. Through this research, it is expected that the palm oil mill's liquid waste can be utilized as a bioactivator for compost production and can be applied to the production of oil palm empty fruit bunch compost.This research was conducted for one year. The stages of the research are as follows: 1. Chemical analysis of POME waste, 2. Making LM POME, 3. Chemical analysis of LM POME, and 4. Making EFB Compost, and Chemical Analysis of oil palm empty fruit bunch compost. Compost making using randomized block design (RBD) with 5 treatments and 4 replications include: P0 = 0 ml / liter of water, P1 = 100 ml / liter of water, P2 = 300 ml / liter of water, P3 = 600 ml / liter of water, P4 = 900 ml / liter of water.The analysis showed that there was an increase in the chemical properties of POME after becoming an LM POME activator. Increased chemical properties such as phosphorus from 0.01 to 0.02, potassium from 0.19 to 0.27, and organic carbon from 0.90 to 1.30, but some chemical properties such as pH decreased from 7.20 to 3, 37 and nitrogen decreased from 0.37 to 0.05. The EFB compost analysis results showed that the highest pH was p2 with a value of 8.23, the highest organic C at p4 treatment with a value of 57.65, the highest total N at p3 with a value of 1.80, P2O5 the highest total at p3 with a value of 0.64, and the highest total K2O at p4 with a value of 2.68.